Some Theorems about (ψ,φ,ϵ,λ)-Contraction in Fuzzy Metric Spaces - Parvin Azhdari (Journal of Mathematics)
We previously proved a number of fixed point theorems for some kinds of contractions like bn-contraction and φ-H contraction in fuzzy metric spaces. In this paper, we discuss the problem of existence of fixed point for (ψ,φ,ϵ,λ)-contraction in fuzzy metric spaces in sense of George and Veeramani.